Evidence-based assessment report outlining seven drivers of zoonotic disease outbreaks and 10 evidence-based recommendations for governments - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The report was officially launched at a press briefing in New York City on 6 July 2020 and is available online. It received extensive global coverage: more than 400 media articles appeared in at least 36 countries and in at least 13 languages.